SISTEM PAKAR PENYAKIT KARET MENGGUNAKAN METODE FORWARD CHAINING PADA PERKEBUNAN PT.WANAMUKTI WISESA TEBO: Expert System;Forward Chaining;Rubber Plant Diseases. - -, Nilawati; -, Riswan; Suana, Irma (LP2M Universitas Nurdin Hamzah, 2020)
Rubber disease is often referred to as OPT (Plant Destruction Organisms) found in rubber plants which cause losses to farmers which interfere with growth and production. The lack of knowledge of rubber farmers about pests (Plant Destruction Organisms) on rubber plants caused significant losses so an expert system was created to diagnose rubber plant diseases using the forward chaining method to obtain the certainty value of a symptom experienced by rubber plants against a disease. The determination of rubber plant disease in this expert system is carried out through a consultation process between the system and the user. The system will display the symptoms of rubber plants by selecting yes / no. Symptoms that are selected by the user will be adjusted to the existing rules so that the user will get the results of disease diagnosis and control. The results of the analysis and evaluation show that the expert system uses this forward chaining approach, reasoning in the expert system starts based on the information provided by the user in the form of existing facts, then the hypothesis is sought based on the facts and existing rules.